STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN KERAPU DI KELURAHAN DJIKOCOBO KOTA TIDORE KEPULAUAN - S. Sangadji, Suwandi; Suhardi, Suhardi (EDUTECH CONSULTANT, 2019)
Therefore, the long-term goal of this research is to find out the strategy of developing groupers aquaculture (Groupers) to maintain business sustainability. Specifically, this research can produce outcomes in the form of policies that can be used by stakeholders as a source of reference. At a minimum, it will be an input for the Regional Government in formulating policies related to the management and development of grouper aquaculture for the realization of the vision of the government of the City of Tidore Islands as an Agromarine-based service city that prioritizes development in agriculture and fisheries. In addition, research results will be published in scientific journals to enrich scientific insights for academics and practitioners. This type of research is descriptive research. The method used in this research is a qualitative method with a case study approach. Through these methods, the data obtained are more in depth and accurate. Data collection is done by observation, interview and study documentation. The data used are secondary and primary data and then analyzed using SWOT analysis.